FRAME WORK MENUJU INDIONESIA RAHMATAN LIL ‘ALAMIN: (Framework Towards Indonesia Rahmatan lil 'Alamin) - Syahrul Efendi Dasopang; Fina Rahmania (Ikatan Sarjana Al-Qur'an Indonesia (ISQI), 2024)
Islam is a religion that is a blessing for all nature. This is in accordance with the mission of Islamic teachings, namely to free humans from various forms of anarchy and injustice. At the value level, Islam from the beginning teaches goodness and noble morality, and at the same time prohibits all evil behavior. The ideal moral ideal of Islam is to build a world in which Muslims and non-Muslims live together enjoying justice, peace, compassion and harmony. Moral ideals are the duty of all elements of society, especially religious leaders and intellectuals, to grasp religious moral messages that can lead to a harmonious life amidst plurality. This research aims to formulate a framework to realize Indonesia rahmatan lil 'alamin. At this level too, character education has a strategic role in achieving Islamic ideals so that its adherents have a pluralistic mindset, not sectarian, let alone discrediting other groups. In this way, Muslims understand the meaning, characteristics and mission of Islam so that people no longer use Islam for personal, group and party interests. In fact, there are no longer any extreme beliefs that use the name of Islam as a cover for the purpose of carrying out acts of terrorism.